2014
DOI: 10.1080/09537325.2014.974530
|View full text |Cite
|
Sign up to set email alerts
|

Exploring perceived control in domestic electricity demand-side response

Abstract: Research into consumer acceptance of domestic electricity demand-side response (DSR) highlights loss of personal control as a key concern. This UK focus group study explored people's perceived control in relation to home energy use and DSR. Three DSR offerings were discussed: fixed and dynamic time of use (TOU) pricing and direct load control. Participants' main motivations for control were costs, comfort, time/flexibility and autonomy. The majority viewed a fixed TOU tariff as increasing personal control, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 16 publications
(14 reference statements)
0
34
0
Order By: Relevance
“…Identity, control, freedom and self-determination are vital ingredients of a home (Blunt & Dowling, 2006). Studies have demonstrated that remote control had a negative impact on the sense of control of householders over their homes (Fell, Shipworth, Huebner & Elwell, 2014).…”
Section: Control and The Smart Grid At Homementioning
confidence: 99%
“…Identity, control, freedom and self-determination are vital ingredients of a home (Blunt & Dowling, 2006). Studies have demonstrated that remote control had a negative impact on the sense of control of householders over their homes (Fell, Shipworth, Huebner & Elwell, 2014).…”
Section: Control and The Smart Grid At Homementioning
confidence: 99%
“…In agreement with the findings of Strengers (2013), our study finds no consensus among engineers and developers of the energy sector as to the scripts of automation and control in smart grid households. A previous study on people's views on remote control (RC) and variable prices based on focus groups has shown that RC can have an effect on the sense of control that consumers have over their home (Fell et al, 2014).…”
Section: Automationmentioning
confidence: 99%
“…The scheme also allows an automatic injection of on-site renewable energy sources as appropriate [31]. The research of smart metering programs in the UK by Fell et al (2014) [32] indicates that consumer acceptance of domestic electricity demand-side response (DSR) highlights the loss of personal control as a critical concern.…”
Section: Literature Reviewmentioning
confidence: 99%